I don’t want martyrdom any more: The case of Bellezze Orsini - Mattarucco, Giada (Kwartalnik Neofilologiczny, 2026)
In 1528, a simple woman from the Sabine countryside was tried for witchcraft. Forced through torture to plead guilty, she committed suicide. Her case would be like many others, except that, along with the trial documents, a confession including a pleading for forgiveness has survived. It appears to be in the woman’s own hand and is written in popular Italian, with clearly regional expressions. The episode invites reflection on issues that are, unfortunately, relevant even today.